A study of acute kidney injury in different poisoning cases in Bundelkhand region - Kuldeep Chandel; Mandavi Agarwal; Mithilesh Kumar; Hitesh Kumar; Medha Singh (Asian Journal of Medical Sciences, 2023)
Background: In Bundelkhand region, 15–18% of patients who are attended in the emergency setting comprises poisoning, 60–70% of which are agriculture-based poisons due to its easy accessibility. The chief complication of poisoning is acute kidney injury (AKI). Aims and Objectives: The aim of the study was to find out the proportion of AKI in acute poisoning, the spectrum of clinical features and their complications and outcome. Materials and Methods: The cross-sectional study was performed in patients admitted in Departments of Medicine, MLB Medical College and Hospital, Jhansi over a period of 25 months (December 2020–October 2022). Results: In our study, there were 100 patients, 83% developed pre-renal AKI and 17% landed up into acute tubular necrosis. Maximum patients recovered, but 13 patients deteriorated, in which most presented after a lag time of 12 h of poison exposure, during the course of management, 5 patients required dialysis (3 peritoneal/2 hemodialysis). Out of 13 Patients, 11 expired and 2 improved, most of them consume celphos and insecticide. Conclusion: Our study shows that agriculture-based chemicals are easily available and accessible for poisoning. The time lag in proper treatment and detoxification leads to various complications; an early intervention and appropriate antidote easily reverses complications and end-organ damage, whereas some cases require dialysis or ventilator support. Middle-aged male, low socioeconomic economic groups, and psychiatric issues lay as background for most poisoning cases, where financial deprivement, lack of knowledge, and awareness have major issues.